PENGARUH PERMAINAN ORIGAMI TERHADAP PERKEMBANGAN MOTORIK HALUS PADA ANAK USIA PRASEKOLAH 3-6 TAHUN DI KELURAHAN PERKAMIL LINGKUNGAN 8 KOTA MANADO - Julita Legi; Winarsi Molintao; Valensia Sumampouw (Yayasan Syalom Cipta Sumikolah, 2025)
Increasing fine motor development in preschool children is very important, because these skills influence various aspects of daily behavior. Children who have good fine motor skills can participate in play activities and interact with peers. This research aims to examine the influence of origami games on the fine motor development of children aged 3-6 years. This research uses a quantitative design with a Quasi experimental design, especially One-Group Pre-Post test Design. With the 16 children samples. The statistical test used is the